2009
DOI: 10.1002/ana.21704
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence of monomer/misfolded superoxide dismutase‐1 in sporadic amyotrophic lateral sclerosis

Abstract: Although SEDI antibody does not necessarily label all misfolded forms of SOD1, these findings show a distinct difference between fALS1 and sALS, and do not support that monomer/misfolded SOD1 is a common disease entity linking all types of ALS. This is important to our understanding of ALS disease pathogenesis and to considerations of the applicability of using therapeutics that target misfolded SOD1 to non-SOD1-related cases. Ann Neurol 2009;66:75-80.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 26 publications
(44 reference statements)
4
81
0
Order By: Relevance
“…Finally, accumulation of misfolded SOD1 has been reported by several groups also in sporadic ALS (27,(41)(42)(43)(44)(45)(46)(47), although other groups have reached the opposite conclusion (48)(49)(50)(51). The identification of MIF as a cytosolic chaperone that stimulates the folding or refolding of misfolded SOD1 and inhibits the aggregation of mutant SOD1 in vivo suggests new avenues for therapy in ALS, mediated by increasing intracellular MIF levels in the nervous system.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, accumulation of misfolded SOD1 has been reported by several groups also in sporadic ALS (27,(41)(42)(43)(44)(45)(46)(47), although other groups have reached the opposite conclusion (48)(49)(50)(51). The identification of MIF as a cytosolic chaperone that stimulates the folding or refolding of misfolded SOD1 and inhibits the aggregation of mutant SOD1 in vivo suggests new avenues for therapy in ALS, mediated by increasing intracellular MIF levels in the nervous system.…”
Section: Discussionmentioning
confidence: 93%
“…Also, alterations in gene expression in the spinal cord were reported for mutant and WT SOD1 models but not in nontransgenic mice (89). Large aggregates of SOD1 are generally observed in fALS, but have only been reported for a subset of sALS cases (4,5,90), and are not detected by SEDI in sALS (90). However, small species of misfolded SOD1 have been proposed to be a common molecular signature in both sALS and fALS (91).…”
Section: Aggregation Arising From Holo Sod1 Is Not Different Frommentioning
confidence: 99%
“…Inhibition of SOD causes accumulation of cellular superoxide radical and leads to free radical-mediated damage to mitochondrial membranes, the release of cytochrome c from mitochondria, and apoptosis of the cancer cells. It is concluded that targeting SOD1 may be a promising approach to the selective killing of cancer cells and that mechanism-based combinations of SOD inhibitors with free radical-producing agents may have clinical applications [23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%